LINGUOCULTURAL FEATURES OF MICROTOPONYMS IN THE CITIES OF LONDON AND TASHKENT - Yuldoshkhonov Javohir Dilshodbek ugli (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This thesis presents a comparative analysis of the linguocultural features of microtoponyms in the cities of London and Tashkent. It examines their formation based on historical, political, and cultural factors, as well as their role in representing urban identity.